Developing the data management component of an academic discipline program for an educational management information system - Ju. V. Starichkova; I. E. Rogov; V. S. Tomashevskaya (Российский технологический журнал, 2023)
Objectives. The need to apply methods and models to support the educational process at universities including the formation and management of academic discipline programs (ADPs) is determined by the growing need for the active implementation of various automation tools including integrated information systems, which arise in response to a number of regulatory and legal factors. Such social factors result in the significant increase in the volume and categories of information circulating within business processes of an educational organization, as well as the expansion of the requirements for ensuring the protection, storage, and transmission of information. In recent years, the Government of the Russian Federation has approved the national “Digital Economy” and “Education” projects (including the Federal Project “Digital Educational Environment”) emphasizing the growing role of informatization and digitalization processes in education. In this connection, an obvious discrepancy arises between the theoretical characteristics of information flows existing in educational organizations and the methods of its collection, processing, storage, analysis, and application used in practice. One of the most important conceptual components of the educational process in higher education institutions is the ADP, which organizes the relationship between various components of the educational process: curriculum, competencies, training areas, learning technologies, and methods for conducting the control check of students’ knowledge. The labor-intensive and variable nature of ADP development and implementation requires the introduction of information technologies. Thus, the aim of the present work is to analyze the volume and structure of institutional educational programs in order to identify the necessary software requirements.Methods. The classification of learning management systems according to various criteria, key requirements for academic disciplines, and ADP structure is considered.Results. An analysis of links between the ADP and key entities of the educational process is presented. The functionality of the self-developed ADP module for implementing at RTU MIREA is aimed at providing interconnection, transparency, and availability of links between academic discipline parameters and its sections.Conclusions. Introducing the ADP module allows reducing the time spent on developing the program by providing universal templates of academic disciplines, along with the possibility of autofilling the academic discipline parameters and tracking the current status of ADPs, as well as increasing the level of awareness of participants in the educational process.